Harnessing the Power of Genomics to Secure the Future of Seafood - Bernatchez, Louis; Wellenreuther, Maren; Araneda, Cristián; Ashton, David T.; Barth, Julia M.I.; Beacham, Terry D.; Maes, Gregory E.; Martinsohn, Jann T.; Miller, Kristina M.; Naish, Kerry A.; Ovenden, Jennifer R.; Primmer, Craig R.; et al. (Trends in ecology & evolution (Amsterdam), 2017)
Best use of scientific knowledge is required to maintain the fundamental role of seafood in human nutrition. While it is acknowledged that genomic-based methods allow the collection of powerful data, their value to inform fisheries management, aquaculture, and biosecurity applications remains underestimated. We review genomic applications of relevance to the sustainable management of seafood resources, illustrate the benefits of, and identify barriers to their integration. We conclude that the value of genomic information towards securing the future of seafood does not need to be further demonstrated. Instead, we need immediate efforts to remove structural roadblocks and focus on ways that support integration of genomic-informed methods into management and production practices. We propose solutions to pave the way forward. Advancements of genetic technologies now allow the collection of genome-wide data in nonmodel species in a cost-effective manner. These genomic-informed technologies allow addressing a comprehensive spectrum of needs and applications relevant to fisheries, aquaculture, and biosecurity. Genomics tools also improve our understanding of how aquatic organisms adapt and respond to the environment, and improve our ability to monitor environmental variation and exploited species. Genomic approaches are now rapidly replacing traditional genetic markers, but their application in fisheries and aquaculture management has stagnated when compared to agriculture where they have long been used for improved production. There is no reason to further delay the application of genomic tools in fisheries management and aquaculture production.